Viral dominance patterns in chronic hepatitis delta determine early response to interferon alpha therapy. Issue 11 (10th July 2018) - Lutterkort, G. L.; Wranke, A.; Hengst, J.; Yurdaydin, C.; Stift, J.; Bremer, B.; Hardtke, S.; Keskin, O.; Idilman, R.; Manns, M. P.; Dienes, H. P.; Falk, C.; et al.
Summary: Chronic hepatitis D is caused by coinfection of hepatitis B and hepatitis D virus. While HDV is the dominant virus over HBV in the majority of cases, mechanisms and consequences of viral dominance are largely unknown. We aimed to investigate associations between viral dominance patterns and patients' characteristics and inflammatory features; 109 HDV‐infected patients treated with PEG‐IFNa‐2α within the international multicentre, prospective HIDIT‐2 trial were studied. Patients were classified as D‐ or B‐dominant if the viral load of one virus exceeded that of the other virus by more than 1log10 . Otherwise, no viral dominance (ND) was described. We used Luminex‐based multiplex technology to study 50 soluble immune mediators (SIM) in pretreatment samples of 105 HDV RNA‐positive patients. Dominance of HDV was evident in the majority (75%) of cases. While only 7% displayed B‐dominance, 17% showed nondominance. D‐dominance was associated with downregulation of 4 interleukins (IL‐2ra, IL‐13, IL‐16 and IL‐18) and 5 chemokines/cytokines (CTACK (CCL27), MCP‐1 (CCL2), M‐CSF, TRAIL and ICAM‐1) while no analyte was increased. In addition, D‐dominance could be linked to a delayed HDV RNA response to pegylated interferon as patients with B‐dominance or nondominance showed higher early HDV RNA responses (61% at week 12) than D‐dominant patients (11%; P  <   .001). In conclusion, this study revealed unexpected effects of viral dominance on clinical and immunological features in chronic hepatitis delta patients. Individualizing PEG‐IFNa‐2α treatment duration should consider viral dominance. Overall, our findings suggest an activated but exhausted IFN system in D‐dominant patients.